Penyuluhan Pemberian Jus Melon Dalam Upaya Pencegahan Anemia Pada Anak Sekolah Dasar - Wahyu Nindi Sayekti; Deby Utami Siska Ariani (AMMA : Jurnal Pengabdian Masyarakat, 2026)
The growth period in elementary school children aged 7 to 12 years requires balanced and sufficient nutrition. Fulfillment of balanced nutrition can be an effort to prevent the risk of anemia in children. Anemia in school children greatly affects the development and cognitive abilities, physical growth and weak body immunity. Melon contains high vitamin C which is an important factor in the absorption of iron in the body. The purpose of this study is to increase children's knowledge in efforts to prevent anemia by drinking melon juice. The research method was a lecture and at the end of the session each child was asked 5 multiple choice questions related to the benefits of melon and the impact of anemia. The number of respondents was 30 children. The results of the study of children's knowledge about the benefits of melon and the impact of anemia were 20 children (66,7%) good knowledge 6 children (20%) sufficient knowledge and 4 children (13,3%) poor knowledge. This counseling is a preventive effort by providing education on preventing anemia in children by consuming melon. The conclusion of this counseling was that the children participated enthusiastically and gained knowledge about the benefits of melon in preventing anemia. The results of this outreach activity showed an increase in understanding of the benefits of melon and the impact of anemia on children, so it is hoped that children will realize the importance of healthy food or drinks for the body.